EVALUASI DINAMIKA KERENTANAN LINGKUNGAN BERDASARKAN KERAPATAN VEGETASI DI DAERAH ALIRAN SUNGAI TABUNIO - Syarifuddin Kadir; Ichsan Ridwan; Wahyuni Ilham; Nurlina Nurlina (Jurnal Hutan Tropis, 2021)
A Watershed is an ecosystem whose first component consists of natural resources vegetation, land, water, and human resources. Tabunio watershed covering an area of 62,558.56 hectares consists of 10 sub-watersheds. The Normalized Difference Vegetation Index (NDVI) is used in vegetation density analysis. Vulnerability of environmental damage is the condition of a region that has the potential for environmental damage due to human activities and or activities that have the potential to cause environmental impacts.The purpose of vegetation density analysis is carried out for the evaluation of environmental vulnerability dynamics in Tabunio watershed, i.e: 1). Knowing changes in land cover; 2. Knowing the classification of vegetation density; 3. Determine efforts to increase vegetation density. The benefits of this analysis are to obtain directives that can have a positive impact on the control of flood suppliers' vulnerability and environmental vulnerability by determining forest and land rehabilitation techniques.Based on the results of mapping and analysis obtained: 1) changes in land cover in 2005-2020 are dominant in forest land cover, open land, settlements, plantations, swamp farming, shrubs, and mining; 2) Vegetation density in the upstream sub-watershed is dominated by the classification of dense and very tight vegetation density; 3) The green revolution of the upstream watershed is dominated for ecological purposes with dense and very close vegetation, the central part of the watershed is dominated for ecological, economic and social with tight vegetation, downstream green revolution watershed dominated for economic and social interests with dense and sparse vegetation